The Battle is the Pay-Off - Ingersoll, Ralph, 1900-1985 (London John Lane The Bodley Head, 1944)
Attempt to describe one battle as it appeared to an American soldier who took part in it
Keywords: World War (1939-1945) -- Tunisia--Tunis